Pertumbuhan Ekonomi, PAD, DAU dan DAK Terhadap Pengalokasian Belanja Modal pada Kabupaten dan Kota di Provinsi Sumatera Barat - Sabri; Endri, Fauziah; Fafika Nengsih, Yeni; nasfi, nasfi (El-kahfi | Jurnal Ekonomi Islam, 2021)
The purpose of this study was to determine the effect of economic growth, regional original income (PAD), general allocation funds (DAU) and special allocation funds (DAK) on the allocation of capital expenditures in districts and cities in West Sumatra province in 2015-2019. This research is an associative research. This research data consists of Economic Growth, namely Gross Regional Domestic Product (PDRB), PAD, DAU, DAK and Capital Expenditures derived from the Realization Report of Regency and City APBD in West Sumatra Province in 2015 – 2019, obtained from the Website of the Central Statistics Agency of Sumatra West. The data is processed by using Partial Least Squares (PLS) analysis technique using smartPLS software. The results of the study show that: Economic growth has an effect and is significant on the allocation of capital expenditures. Regional Original Income has an effect and is significant on Capital Expenditure Allocation. The General Allocation Fund has an effect and is significant on the allocation of capital expenditure, and the special allocation fund has an effect and is significant on the allocation of capital expenditure.